MEMAHAMI PROSES PENGREKRUTAN DAN SELEKSI, JENJANG KARIR DAN PANGKAT DALAM KEPOLISIAN - Artika Cesar Aura Devi; Chyntia Martini; Nadia Karin; Zahra Permata Sari; Tugimin Supriyadi (ADMIN: Jurnal Administrasi Negara, 2024)
The National Police of the Republic of Indonesia (Polri) is an institution that plays a crucial role in maintaining public security and order. The recruitment and selection process in the police force is a very critical initial stage to ensure that only qualified candidates are accepted. The recruitment process includes announcements, registration, administrative selection, physical selection, written tests, psychological tests, interviews, and medical examinations. Psychological tests are important to assess the emotional stability and character of the candidates. The "Good Cop and Bad Cop" interrogation technique is often used in investigations. The career path in Polri is divided into Tamtama, Bintara, and Perwira, with each level having specific promotion criteria. The stringent recruitment and selection process ensures that only qualified individuals are accepted as members of Polri. A structured career path helps in the professional development of members and builds public trust in Polri. Transparency and accountability in this process are essential to prevent nepotism and corruption.